Studies on The Antibacterial Effect of The Ethanolic Extracts of Cnidoscolus aconitifolius (Miller) (Hospital Too Far), Piliostigma thonningii (Schum) (Camels Foot) And Lantana camara (Linn) (Lantana) - Nyam M.A.; Abdullahi, U.I.; Atsen, E.; Itelima, J.U. (Journal of Medical Biomedical and Applied Sciences, 2020)
Studies were carried out at National Veterinary Research Institute (NVRI) Vom Jos, Plateau State on antibacterial activities ofethanolic leaf and stem extracts of Cnidoscolusaconitifolius, Piliostigmathonningiiand Lantana camara to verify claims by locals of their medicinal properties. Standard cold maceration qualitative biochemical analysis and agar well diffusion methods were used. All extracts were effective against gram positive and gram negative bacteria with the exception of Shigelladysenteriaewhich showed resistance against four extracts but was highly positive against the extracts of Piliostigmathonningii.A positive control Ciprofloxacin was tested against all clinical isolates producing a broad spectrum of activity, positive zones of inhibition were screened for minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Results of biochemical screening of the test plants revealed the presence of alkaloids, tannins, flavonoids, carbohydrates, steroids, anthraquinones, and cardiac glycosides, with saponins only present in Piliostigmathonningii stem and Lantanacamara leaf extracts. Sensitivity test was carried out against two gram positive bacteria.Bacillussubtilisand Staphylococcusaureus, and three gram negative bacteria Escherichia coli, Salmonella typhi and Shigelladysenteriae. From the results of these findings, the activity of the extracts might be concentration-dependent because all the best activities were seen at the highest concentration (200mg/ml) and therefore, work on higher concentrations and purification of the crude extracts is recommended to achieve considerable antibacterial activity. The results provided scientific backing to the use of these plant extracts by the locals in the treatment of conditions usually associated with the organisms tested.